Vallási identitásterek? Teológiai töredékek az identitás kérdéséről - Ferencz, Árpád (Studia Litteraria, 2021)
The central question of this study is the question of the identity from a special perspective. What has the identity of the church, or with other words: what has the religious identity to do with public spaces? The question of the identity became one of the most important questions of theology in the 21st century. Does the church have an identity crisis today? If yes, what is the manifestation of this crisis? The present study is focusing on different identity-constructions and on the question, how the church can create an own place on the present “religious market”. With reference on the studies of Niklas Luhmann, Jürgen Habermas and the Theologians Karl Barth, Eric Peterson and others the following thesis is verified: the Christian religion has an alternative space in the public space, the so called “eschatological publicity”. The consequence of this kind of publicity is that Christian religion is able to create a sort of “anti-space” against the mainstream places and against the simplified mainstream discourse in society.